The Cost Effectiveness of Single-Patient-Use Electrocardiograph Cable and Lead Systems in Monitoring for Coronary Artery Bypass Graft Surgery - Saunders, Rhodri; Lankiewicz, Julie (Frontiers in Cardiovascular Medicine, 2019)
Background: During admission for coronary artery bypass graft (CABG) surgery patients receive electrocardiograph (ECG) monitoring; for which reusable ECG cable and leads (rECG) are standard. Objective: Evaluate the cost effectiveness of a single-patient-use ECG cable and lead system (spECG). Methods: Review of the Medicare 2011-2014 database followed by a cost-effectiveness model considering a Medicare facility transitioning from rECG (9 per patient) to spECG (15). In-hospital ECG monitoring was for ≤8 days. In the model, patients underwent CABG and recovered in the intensive care unit, before transfer to the general ward and discharge. Surgical site infection (SSI) resulted in increased length of stay, readmission, or outpatient care. Health outcomes impacted EQ-5D-measured quality adjusted life years (QALYs). Health and cost outcomes were discounted at 3.5% annually. All costs in 2016 USD. Significance (95% level) was assessed via 2,000 simulations. Results: In 2014, 5.49% of patients had an SSI by 90-days post-surgery, with spECG reducing the odds of an SSI (odds ratio: 0.74, 0.62-0.89). Mean 40-year, per-patient costs to Medicare were 65,497 with rECG and 65,048 with spECG. The 450 saving was significant, with a median (95% credible interval) reduction of 466 (174 to 989). Cost drivers were days required to treat inpatient SSIs. QALYs increases with spECG were significant but minor (median increase 0.008). Medicare savings may total 40 million per year with use of spECG. Conclusions: Post-operative SSI is a concern for Medicare patients undergoing CABG, and use of spECG is likely to provide cost and patient benefits.